Changing China, Changing Africa: Future Contours of an Emerging Relationship. (July 2014) - Davies, Martyn; Draper, Peter; Edinger, Hannah
<x xml:space="preserve">Abstract</x> Current China–Africa relations have been statically framed: China invests in the continent and exports resources extracted by its state‐owned enterprises and fuelled by aid flows, while simultaneously undercutting African industry through cheap exports. We frame this debate, then explore how the framework could adjust in response to changing economic realities in China, centered on the "rebalancing" of the growth model toward domestic consumption. We argue that a new wave of private sector‐led, low‐cost manufacturers may find its way to selected African shores, in the process transforming those economies and the way in which China interacts with them, both for the better.